Organizational behavior improving performance and commitment in the workplace - Colquitt, Jason; LePine, Jeffery A.; Wesson, Michael J. (New York, NY McGraw Hill, 2023)
"Organizational behavior (OB) remains a fascinating topic that everyone can relate to (because everyone either has worked or is going to work in the future). What makes people effective at their job? What makes them want to stay with their employer? What makes work enjoyable? Those are all fundamental questions that organizational behavior research can help answer. However, our desire to write this text also grew out of our own experiences (and frustrations) teaching OB courses using other texts. We found that students would end the semester with a common set of questions that we felt we could answer if given the chance to write our own book"--
Includes index.
Keywords: Consumer satisfaction; Job satisfaction; Organizational behavior; Personnel management; Strategic planning